1996
DOI: 10.1557/jmr.1996.0160
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of Nb thin films on sapphire

Abstract: The Nb/α−Al2O3 system has been used as a model study for investigating the stability of different MBE grown epitaxial Nb films on α−Al2O3 substrates. The films were grown at 800 °C in ultrahigh vacuum. The growth process was monitored in situ by reflection high energy electron diffraction (RHEED). After deposition the structure of the film was investigated by x-ray diffraction (XRD) and conventional transmission electron microscopy (CTEM) which encompasses also selected area diffraction (SAD). Both techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…[7][8][9] No detailed information is available in the literature on the growth mode of Nb on the basal plane at high temperatures. [7][8][9] No detailed information is available in the literature on the growth mode of Nb on the basal plane at high temperatures.…”
Section: A Film Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] No detailed information is available in the literature on the growth mode of Nb on the basal plane at high temperatures. [7][8][9] No detailed information is available in the literature on the growth mode of Nb on the basal plane at high temperatures.…”
Section: A Film Growthmentioning
confidence: 99%
“…1,3,12 The orientation in which Nb clusters nucleate on the (0001)a -Al 2 O 3 surface will be strongly IP address: 152.14.136.77 influenced by differences in interfacial energies. As shown in a recent publication, 7 For a single island, a critical thickness or height h crit can also be defined. 7 the sapphire substrate.…”
Section: A Film Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…4 One feature of the niobium/sapphire system that makes it unique is the three-dimensional relationship between metal and substrate, first discovered by Durbin et al 5 and confirmed by a number of others, This relationship is by no means universally observedunder certain growth and annealing conditions other orientational relationships have been found. [11][12][13][14] However, Zhao et al go one step further, calling into question the validity of this relationship and instead proposing their own threedimensional registry. My comment begins with a summary of their arguments.…”
mentioning
confidence: 99%
“…49 Similar results have been found for niobium thin films (150 nm) grown on c-plane sapphire using MBE techniques at 800°C, and may be useful in explaining the mechanism of film reorientation. 50 After film deposition the orientation relationship found between the niobium film and the sapphire using Reflection High Energy Electron Diffraction (RHEED) showed the (111) planes of niobium parallel to the (0001) planes in the sapphire. During anneals at 1500°C for times ranging between 1 min and 4 h small grains of niobium embedded in the film with the (110) planes parallel to the (0001) planes in sapphire completely consumed the film.…”
mentioning
confidence: 99%